The politics of marriage in medieval India : gender and alliance in Rajasthan - Singh, Sabita
This volume seeks to highlight the multicultural ethos of India and its regional variations, by studying different aspects of marriage in Rajasthan. The social structure, the caste positions, the emergence of Rajputs, etc., have been looked into. Customs and practices such as dowry, polygamy, child marriage, and concubinage are examined too.